Latest Quaternary paleoseismology and slip rates of the Longriba fault zone, eastern Tibet: Implications for fault behavior and strain partitioning. Issue 2 (29th April 2013) - Ren, Junjie; Xu, Xiwei; Yeats, Robert S.; Zhang, Shimin
Abstract [1] Although much work has been done on active tectonics of eastern Tibet, little is known about the Longriba fault zone and its role in strain partitioning. Whether its two sub‐parallel strands (Longriqu and Maoergai faults) can rupture simultaneously in a large earthquake remains unknown. We conducted trenching combined with the interpretation of satellite imagery, field investigations, topographic surveys, and radiocarbon and Optically Stimulated Luminescence (OSL) dating to reconstruct paleoseismic history, and we used displaced terrace risers to estimate geological slip rates. Our results demonstrate that the Longriba fault zone is predominantly right‐lateral with a small southeast‐verging thrust component. Four surface‐rupturing events occurred on the Longriqu fault at 5080 ± 90, 11, 100 ± 380, 13, 000 ± 260, and 17, 830 ± 530 cal yr B.P. Together with our previous trenches on the Maoergai fault, we found that the last event probably ruptured both the Longriqu and Maoergai faults. Prior to the last event, the two strands of the Longriba fault zone experienced alternating earthquakes. The fault zone has a high potential for an earthquake larger than Mw 7. The slip rate of the Longriba fault zone decreases from ~7.5 mm/yr in latest Pleistocene to ~2.1 mm/yr in the Holocene, probably related to a slowing down of the eastern motion of the Tibetan Plateau. The comparison with slip rates at the Longmen Shan fault zone suggests that the Longriba fault zone has an equally important role in strain partitioning in eastern Tibet. This study is helpful to seismic hazard assessment and an understanding of deformation mechanism in eastern Tibet.